2000
DOI: 10.1063/1.126402
|View full text |Cite
|
Sign up to set email alerts
|

Experimental test for elastic compliance during growth on glass-bonded compliant substrates

Abstract: Highly mismatched films (In 0.44 Ga 0.56 As, 3% mismatch͒ grown well beyond their critical thickness ͑to 3 m͒ on GaAs glass-bonded compliant substrates exhibit surfaces four times smoother and strain distributions twice as narrow as films grown simultaneously on conventional GaAs substrates. The compliant substrates consist of a thin ͑ϳ10 nm͒ GaAs template layer bonded via a borosilicate glass to a mechanical handle wafer. The improvement of highly mismatched films grown well beyond their critical thickness on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The relative thickness of the film and template layers, in conjunction with the mismatch strain, e 0 , determines the residual strain, e x (0,t), in the elastic overlayer. If the thin template layer were mechanically decoupled from the handle wafer, the mismatch strain would partition between the template and film (assuming that the elastic modulii of the film and template are identical) according to the expression: 6,7 e e feq f…”
Section: A 1-d Model For the Kinetics Of Film Relaxation Due To A Vismentioning
confidence: 99%
See 1 more Smart Citation
“…The relative thickness of the film and template layers, in conjunction with the mismatch strain, e 0 , determines the residual strain, e x (0,t), in the elastic overlayer. If the thin template layer were mechanically decoupled from the handle wafer, the mismatch strain would partition between the template and film (assuming that the elastic modulii of the film and template are identical) according to the expression: 6,7 e e feq f…”
Section: A 1-d Model For the Kinetics Of Film Relaxation Due To A Vismentioning
confidence: 99%
“…Previous publications have demonstrated that if this thin template layer is mechanically decoupled from the handle wafer such that it can move in the plane of the bonded interface, strain can be partitioned from the film to the template layer before the onset of plastic deformation in the growing film. 6,7 Kinetics of Strain Relaxation in Semiconductor Films Grown on Borosilicate Glass-Bonded Substrates Changes in the strain relaxation of semiconductor films due to growth on a thin epitaxial template bonded via a borosilicate glass to a mechanical handle wafer have been observed. A kinetic analysis of the mechanical decoupling between the film/template heterostructure and the handle wafer is developed in order to estimate and evaluate the contribution of glass viscous deformation to the observed strain relaxation.…”
Section: Introductionmentioning
confidence: 98%
“…While it is recognized that a significant reduction in the misfit dislocation density threading into heteroepitaxially grown films has been achieved for a wide range of materials systems, the mechanism for long-range accommodation of the mismatch into the substrate layer is not well understood, and there is considerable dispute about it [85,86]. Much of the work to date has been limited to TEM observations confirming limited misfit dislocation densities, but full characterization of the degree of relaxation in the heteroepitaxially grown layers is frequently lacking.…”
Section: Substrate Engineering-the Road To New Materialsmentioning
confidence: 99%
“…1 However, GaAs bonded to oxide layers is also being investigated for the integration of GaAs and Si or for the development of structures such as glass-bonded compliant substrates. [2][3][4] For these applications, the native or thermally grown oxide on GaAs is not useful. As a result, oxidebonding media are formed by a variety of other deposition techniques.…”
Section: Introductionmentioning
confidence: 99%